Uterine Manifestation of Sarcoidosis Diagnosed in the Setting of Fever of Unknown Origin - Utsunomiya-Nishimizu R; Tsutsui Y; Horinouchi N; Yoshimura K; Nishida M; Shiota S; Miyazaki E (International Medical Case Reports Journal)
Rie Utsunomiya-Nishimizu,1,2 Yuki Tsutsui,1 Noboru Horinouchi,1,2 Katsuhiko Yoshimura,1 Masakazu Nishida,3 Seiji Shiota,1,2 Eishi Miyazaki1,2 1Department of General Medicine, Oita University Faculty of Medicine, Oita, Japan; 2Center for Community Medicine, Oita University Faculty of Medicine, Oita, Japan; 3Department of Obstetrics and Gynecology, Oita University Faculty of Medicine, Oita, JapanCorrespondence: Eishi Miyazaki, Department of General Medicine, Oita University Faculty of Medicine, 1-1 Idaigaoka, Hasama-machi, Yufu-shi, Oita, 879-5593, Japan, Tel +81-97-586-5106, Fax +81-97-549-6502, Email eishida@oita-u.ac.jpAbstract: We report a rare case of uterine sarcoidosis. A 28-year-old woman presented with periodic fever over 38°C for the past 5 months. One year prior, splenomegaly was noted. The serum angiotensin-converting enzyme levels were elevated; however, the lungs, lymph nodes, eyes, and skin appeared normal. Fluorine-18-fluorodeoxyglucose positron emission tomography revealed accumulations in the uterine body and spleen. Magnetic resonance imaging showed multiple irregular uterine masses. Intraoperative frozen section assessment of the uterine masses suggested sarcoma; therefore, total hysterectomy was performed. However, formalin-fixed specimens of the resected organs revealed noncaseating epithelioid cell granulomas in the myometrium and fallopian tubes, indicating the final diagnosis of uterine sarcoidosis. Clinicians should recognize that sarcoidosis can affect the uterus.Keywords: sarcoidosis, female genital tract, uterus, fever of unknown origin, fluorine-18-fluorodeoxyglucose-positron emission tomography